Exploring Teaching Roles and Responsibilities in Adult Literacy Education: Do Teachers See Themselves as Transformative Educators? - Karen M. Margo (Adult Education Research Conference, 2002)
This qualitative study compared English and ESL teachers’ perspectives of teaching and learning with the role of the adult educator and the process of learning, most notably described by Jack Mezirow in his theory of transformational learning and Paulo Freire in his critical theory of adult education. Significant parallels between some of the teachers’ intentions, views of learning, and curriculum orientation were consistent with the role of the educator and the process of learning described in transformative theories of adult learning. The teachers in this study also held many reservations about the role of the teacher as a change agent.